Children and youth in street situations and their capabilities: "from strategies of urban survival to careers within the protection system" - Ryckmans, Jean-Christophe (Educateurs et préventions, 2020)
This research uses an Interactionist approach to understand how children and youth in street situations in Nepal and elsewhere negotiate their social identity while confronted with dynamics of domination, labelling and violence. Their capability to survive on the street determines their career, which is also influenced by their capacity to play with the institutional network supposed to help or control them. Presenting a typology of the existing intervention system, this research will shed light on the existing gaps and the effect of conversion « back to the norm », carried out or encouraged by NGOs or public authorities